2020
DOI: 10.21203/rs.3.rs-19263/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Positional repeatability and variation in internal and external markers during volumetric-modulated arc therapy under end-exhalation breath-hold conditions for pancreatic cancer patients

Abstract: Background: To assess the positional repeatability of internal and external markers among multiple breath-hold (BH) sessions and assess the positional variation of these markers within BH sessions for volumetric-modulated arc therapy (VMAT) for pancreatic cancer patients. Methods: A total of 13 consecutive pancreatic cancer patients with an internal marker were enrolled. Single full-arc coplanar VMAT was delivered under end-exhalation (EE) BH conditions, while monitoring the internal marker with kilovoltage (k… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Patients held their breath according to the operator's instruction only without visual feedback. This was done in accordance with a previous study where further details can be found 32 …”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…Patients held their breath according to the operator's instruction only without visual feedback. This was done in accordance with a previous study where further details can be found 32 …”
Section: Methodsmentioning
confidence: 89%
“…This was done in accordance with a previous study where further details can be found. 32 The gross tumor volume (GTV) included the primary tumor and metastatic lymph nodes. The clinical target volume (CTV) was defined as the GTV plus a 5 mm margin and the potential para-aortic lymph node and neuroplexus involvement between the celiac axis and the superior mesenteric artery.…”
Section: Initial Planning Ct Acquisition Contouring and Daily Cbct Ac...mentioning
confidence: 99%
“…There are many reports on internal errors in external radiation therapy for LAPC, [17][18][19][20] and many problems need to be solved. It has been pointed out that changes in GI tract density are more affected by particle therapy.…”
Section: Discussionmentioning
confidence: 99%